Regionalisation through economic integration in the Southern African Development Community SADC (SADC) / Amos Saurombe - Saurombe, Amos (2015)
The regional economic community (REC) of the Southern African Development Community (SADC) compri'ses 15 Southern African countries. The' economic and political aspects of regional integration in SADC dictate the pace of integration while the influence of a legal regime for regional integration remains at the periphery. While the SADC Treaty and its Protocol on Trade are clear about the priority of economic integration; the full implementation of SADC's economic integration is still yet to be realised using these legal instruments. Regional economic integration is also a priority at both continental and global level. The legal instruments applicable at these levels are those established through the African Union (AU) and the World Trade Organisation (WTO) respectively. Analysis of these external legal instruments is relevant because SADC Member States are signatories to agreements establishing these organisations·. Thus, rules based trade in SADC should be understood from a regional, continental and global perspective where a community must have well-structured and managed relations between itself and other legal systems as a necessary condition for its effectiveness. These structured relations refers to a legal and institutional framework that defines the relations between community and national laws, spelling out the modalities for implementing community law in Member States, defines the respective competencies of the community and Member States and provide rule based systems for resolution of conflicts. In setting the scene for an in-depth discussion of the legal and institutional framework for regional economic integration in SADC, this study presents the history of SADC, its political and economic characteristics that have shaped the legal aspects of trade within the region, the continent of Africa and the world at large. Within this context, the definition of regional integration is presented from a general and international understanding but ultimately gets narrowed down to what it means for Africa and SADC. The discussion on the · theories behind regional economic integration gives understanding to the integration approach employed in the organisation. South Africa's economic and political leadership is critical in the realisation of economic integration; hence this study acknowledges that without South Africa's full commitment; regional economic integration will suffer .a setback. Besides the challenge of implementing rules based trade in SADC, this study also identifies a number of obstacles to SADC regional economic integration and multiple memberships are identified as a: major stumbling block. A comparative study of SADC's institutional framework with that of the E1;Jropean Union· (EU) is undertaken to establish the rationale behind SADC's choice of utilising the EU model of integration. This study establishes the critical role institutions play in the implementation of treaty obligations as established by the agreements. The main lesson from this comparative study is that the EU institutions are allowed to fulfill their obligations of implementing treaty provisions, while SADC institutions are handicapped. The future of SADC is presented within the context of a set of recommendations that identifies the tripartite free trade area (FTA) that includes the East Africa Community (EAC) and the Common Market for Eastern and Southern Africa (COMESA) as one of viable legal instrument for deeper integration in SADC and the continent of Africa. General recommendations are made on the need for reform of rules and principles that are necessary for the implementation of SADC Treaty regime as well as possible improvements that are important for the full realisation of regional economic integration. === PhD (Law), North-West University, Potchefstroom Campus, 2012